Potentials of Home-made Concoction as Nutrient Solution in a Modified Hydroponic System - Rosit, James Francienne; Pascual, Pet Roey; Rio, Jessa; Sacamay, Meriam Mae; Alferez, Roger; Camomot, Leonilla (JPAIR Multidisciplinary Research, 2015)
A Hydroponic System is a technique that is widely used in Agriculture especially in growing plants in urban areas. A study was conducted to determine the responses of lettuce grown under a modified hydroponic system to different organic solutions at Cebu Technological University – Barili Campus, Philippines.The treatments used in the study are T0 – commercial organic amino acid, T1 – Home-made concoction, T2 – Inorganic fertilizer and T3 - coconut water. Results showed that on the number of leaves, lettuces that were applied with home–made concoction had 10.13% and 15.23% more leaves than inorganic fertilizer and commercial organic amino acid applied treatments respectively (4th week). No significant difference were observed among commercial organic amino acid, home-made concoction and inorganic fertilizer, in terms of leaf length from the 2nd week to 4th week having. Furthermore, comparable results were observed between lettuce applied with home-made concoction and inorganic fertilizer on its leaf width on the 2nd week having 7.03 cm and 6.30 cm respectively. Moreover, comparable effects were also observed on commercial organic amino acid and home-made concoction in plant height having an average length of 17.03 cm and 17.00 cm, respectively. At harvesting, lettuces that were applied with home-made concoction had the heaviest weight having 43.23 g or 20.12% heavier than those applied with commercial organic amino acid and 23.67% heavier than inorganic fertilizer. Therefore, the home-made concoction is the best organic nutrient source in growing lettuce in a modified hydroponic system.
Keywords: Agriculture; modified hydroponic system; organic liquid solution; experimental; research; Cebu; Philippines